LAS NTIC EN LA INNOVACION EDUCATIVA DE LA FCA DE LA UNMSM: EXPERIENCIAS DE VIRTUALIZACIÒN DE LA DOCENCIA - Bedriñana Ascarza, Aquiles (2006)
The New Technologies of Information and Communication (NTIC) as support and basis of the society of the knowledge, are generating paradigmatic changes in the University processes, for which it is important the educational innovation and the integration of the technology in the university teaching-learning process. The Faculty of Administrative Sciences of Universidad Nacional Mayor de San Marcos (UNMSM) is in full load process of reform and curriculum innovation. In this context, we are carrying out studies for the implementation of the virtual modality of teaching. Being aware that traditional teaching in our university does not respond totally to the demands of the current society, we consider that it is urgent to undertake the virtualization of the university as a strategy to achieve student’s insertion in the globalized world. The general objective of this work is to generate a participatory and conceptual frame for the logical and physical design of the Virtual Campus of the Faculty of Administrative Sciences. The specific objective is the investigation on the impact of the first experience of virtualization carried out in our faculty through the use of the interactive Moodle platform.